2020
DOI: 10.3390/ijerph17186638
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Alveolar Ridge Remodelling Post-Extraction Using Sequential Intraoral Scanning over a Period of Four Months

Abstract: The potential applications of computer-aided design/computer-aided manufacturing (CAD/CAM) and intraoral scanning exceed the delivery of standard prosthodontic interventions. The aim of this study was to clinically present a developed assessment technique, that relies on the use of sequential intraoral scanning, three-dimensional superimposition, and 2D and 3D deviation analyses based on a standardised protocol, as an auxiliary tool in monitoring dimensional changes of residual ridge post-extraction with a fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Retrospective Analysis at 6 years of Follow-up. Open Access J Dent Oral Surg 3: 1035 [14] states that in the first seven days after extraction, the greatest dimensional changes occur in the alveolar ridge with the mean maximum negative deviation, identified by 3D analysis, a bone loss of -1.7 mm ± 0 was recorded. , 3, compared to day 0 and the mean 3D reduction in alveolar ridge width was -3 mm at four months compared to one week data.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective Analysis at 6 years of Follow-up. Open Access J Dent Oral Surg 3: 1035 [14] states that in the first seven days after extraction, the greatest dimensional changes occur in the alveolar ridge with the mean maximum negative deviation, identified by 3D analysis, a bone loss of -1.7 mm ± 0 was recorded. , 3, compared to day 0 and the mean 3D reduction in alveolar ridge width was -3 mm at four months compared to one week data.…”
Section: Discussionmentioning
confidence: 99%
“…In in vivo bone regeneration, this novel composite scaffold sustained TSA release and induced robust bone regeneration in a mouse model of calvarial defects. Although this evidence has demonstrated that chitosan biphasic calcium phosphate loaded with trichostatin A (CS/ BCP/TSA) scaffolds can stimulate bone regeneration, controversies remain regarding its application in tooth extraction sockets because the bone remodeling process of the alveolar bone is different from that of other bone areas [28,29] In this study, we hypothesized that released TSA may be an essential osteogenic factor of the scaffold, and this epigenetically modulated scaffold may be used as an alveolar ridge preservation material after tooth extraction [30]. Therefore, we investigated the biological properties of released TSA using a pre-osteoblast cell line and evaluated the alveolar bone healing of tooth extraction sockets filled with CS/BCP/TSA scaffolds compared to conventional bone graft materials in a rat tooth extraction model.…”
mentioning
confidence: 99%